Chilean Challenges in Underground Mining - Electronic Initiation System (IS) and Drill &Blast Engineering Focused Projects - Manuel Calderón (International Society of Explosives Engineers)
Chile is responsible for 30% of the global copper production; the world ́s largest. However, significant challenges are faced in this industry; declining grades (1.13% in 2002 to 0.61% in 2015), high cost of energy, scarcity of water, and environmental concerns. Mining trends suggest the future of the industry will be focused in the underground space, specifically due to the depletion of economically viable surface mineral deposits. For example, the largest block cave mineat Codelco ́s Chuquicamata mine is expected to reduce energy costs by 50% and dust emissions by 97%compared to the open cut mine. To access these underground deposits, critical infrastructure is required; horizontal tunnel developments, extraction levels, vertical raises, and ore passes with the on-time delivery of the highest quality outcomes being a requisite for successful project delivery (Lift 1 of 3 at Chuquicamata Underground has over 1000drawbells).One aspect that makes this scenario even more challenging for deeper underground operations is the increased risk profile (people, equipment, and geotechnical) that forms part of the general environment. Furthermore geotechnical risks should be considered and they include rock burst and windblast. The safe interaction with this environment must be sustainable throughout the full life of the project. This paper presents the Enaex group approach to addressing the blasting challenges and outlines the solutions created. Aspects such as rock mass damage occurrence as a function of blast vibration frequency content has been studied, as well as the development of blasting methodologies for guaranteeing the full 100% extraction of all infrastructure blasts, including the all-important draw bell volumes. The development of such infrastructure volumes in one single event using electronic detonators and the associated achievement of ambitious productivity goals, are described as a critical part of the successful construction of one of the most ambitious UG projects currently present on the world.